2020
DOI: 10.1183/23120541.00361-2019
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette-related cadmium and environmental pollution exposure are reflected in airway ultrafine particle content

Abstract: IntroductionParticulate matter (PM) and cigarette-related cadmium exposure increases inflammation and smokers' susceptibility to developing lung diseases. The majority of inhaled metals are attached to the surface of ultrafine particles (UFPs). A low inhaled UFP content in exhaled breath condensate (EBC) reflects a high inflammatory status of airways.MethodsEBC was collected from 58 COPD patients and 40 healthy smokers and nonsmokers. Participants underwent spirometry, diffusion capacity, EBC and blood samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…In addition, a low UFP level in EBC was an independent predictor of frequent exacerbations (OR = 3.6, 95% CI 1.06–7.97; p = 0.04). Therefore, a low UFP level in EBC has potential as a biomarker of COPD exacerbation and high PM exposure [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a low UFP level in EBC was an independent predictor of frequent exacerbations (OR = 3.6, 95% CI 1.06–7.97; p = 0.04). Therefore, a low UFP level in EBC has potential as a biomarker of COPD exacerbation and high PM exposure [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies are listed in Table 3. Three studies [36][37][38] had a high risk of bias in the possibility of target group comparisons domain, and another [38] in the confounders domain. One study [39] had a high risk of bias in the exposure measurement domain, and another [38] in the outcome domain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, in this review, we summarized the possible role of biomarkers linked to COPD according to four representative types of biological plausibility in patients with COPD exposed to PM through a qualitative review. Among 22 studies, six were found to be relevant regarding biomarkers exploring oxidative stress ( 22 - 24 , 37 - 39 ); one study investigated the roles of innate and adaptive immune systems ( 25 ); and 17 studies investigated genetic regulation ( 26 - 32 , 34 - 36 , 38 - 42 ) and epigenetic regulation of inflammation ( 27 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, various other biomarkers, such as tumor necrosis factor α (TNFα) ( 28 , 33 , 34 , 41 ), circulating vascular cell adhesion molecule-1 (sVCAM-1) ( 26 , 29 , 30 ), fibrinogen ( 41 ), hepatocyte growth factor ( 41 ), ultrafine particle concentration in exhaled breath ( 42 ), and exhaled hydrogen sulfide ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…The findings of low UFP concentrations in EBC and high UFP concentrations in the serum of COPD patients compared with healthy controls serve to support our hypothesis. 5 The concept that UFP translocate to circulation was first proposed by the findings of a murine model in which the induction of lung inflammation resulted in a shift of the UFP pattern towards larger particles, a process which can be explained by translocation of smaller particles thorough inflamed epithelium. 6 In order to further investigate the trajectory of…”
Section: Introductionmentioning
confidence: 99%